Coletânea Internacional De Pesquisa Em Ciências Da Saúde Vol.01 2022
DOI: 10.56238/sevcipcsv1-054
|View full text |Cite
|
Sign up to set email alerts
|

Custos de eventos adversos a medicamento em pacientes hospitalizado

Abstract: Doutor em Engenharia e Gestão do Conhecimento (UFSC). Pós-Doutor em Gestão do Conhecimento (UFSC). Docente, pesquisado e orientador do Programa de Pós-graduação em Educação da Universidade Alto Vale do Rio do Peixe (UNIARP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study conducted by Nascimento et al 31 showed that the adverse events related to the identified medications resulted in a financial impact of R$ 96,877.90 for the institution participating in the research, for society and the Unified Health System (Sistema Único de Saúde-SUS). Of these events, 25 could have been avoided.…”
Section: Discussionmentioning
confidence: 99%
“…The study conducted by Nascimento et al 31 showed that the adverse events related to the identified medications resulted in a financial impact of R$ 96,877.90 for the institution participating in the research, for society and the Unified Health System (Sistema Único de Saúde-SUS). Of these events, 25 could have been avoided.…”
Section: Discussionmentioning
confidence: 99%